2008
DOI: 10.1007/s00259-008-0788-z
|View full text |Cite
|
Sign up to set email alerts
|

Detection of bone metastases in patients with prostate cancer by 18F fluorocholine and 18F fluoride PET–CT: a comparative study

Abstract: FCH PET-CT may be superior for the early detection (i.e. bone marrow involvement) of metastatic bone disease. In patients with FCH-negative suspicious sclerotic lesions, a second bone-seeking agent (e.g. (18)F fluoride) is recommended. (18)F fluoride PET-CT demonstrated a higher sensitivity than (18)F FCH PET-CT, but the difference was not statistically significant. Furthermore, (18)F fluoride PET could be also negative in highly dense sclerotic lesions, which presumably reflects the effect of treatment. It wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
88
0
11

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(102 citation statements)
references
References 15 publications
3
88
0
11
Order By: Relevance
“…Obviously, there seems to be no uniform radiological criteria for assessing intercorporal fusion by plain radiographs or CT [10,[15][16][17][18]. 18F-fluoride PET/(CT) on the contrary has mostly been used in the assessment of malignant bone abnormalities [19][20][21][22][23]. However, promising results are also found in benign bone disorders, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, there seems to be no uniform radiological criteria for assessing intercorporal fusion by plain radiographs or CT [10,[15][16][17][18]. 18F-fluoride PET/(CT) on the contrary has mostly been used in the assessment of malignant bone abnormalities [19][20][21][22][23]. However, promising results are also found in benign bone disorders, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Fluoride has high affinity for bone, with increased uptake reflecting osteoblastic activity [28]. Studies have suggested that fluoride PET may have better sensitivity, specificity, and accuracy in detecting skeletal metastasis compared to choline PET [30].…”
Section: Imagingmentioning
confidence: 99%
“…13,17,[22][23][24][25][26][27][28] Husarik et al 13 reported the sensitivity of choline-PET/CT was 70 per cent with a PSA ≤2ng/ml at the time of the scan, compared with 86 per cent when PSA >2ng/ml. Another group showed a sensitivity of 20 per cent with PSA ≤1ng/ml, 44 per cent for PSA 1-5ng/ml and 82 per cent for PSA >5ng/ml.…”
Section: Trends In Urology and Men's Health May/june 2014mentioning
confidence: 99%
“…The specificity benefit results from the absence of tracer uptake in chronic degenerative lesions that may be falsely positive on bone scans. 17 It has been suggested that PET/CT imaging can identify bone metastases at an earlier marrow-only stage of involvement, before such disease can be identified on CT imaging. 4 No evidence has yet shown the superiority of choline-PET over standard systemic staging imaging techniques in establishing the presence of metastatic disease at diagnosis.…”
Section: M-stagingmentioning
confidence: 99%